2021
DOI: 10.4103/sjmms.sjmms_79_20
|View full text |Cite
|
Sign up to set email alerts
|

Work and school absenteeism in inflammatory bowel disease patients in Jeddah, Saudi Arabia: A cross sectional study

Abstract: Background: Inflammatory bowel disease (IBD), which can have a considerable effect on quality of life, productivity and performance, is typically diagnosed during periods of life in which patients have academic and career-related responsibilities. Objective: The objective of the study was to determine the effect of IBD symptoms on work and school absenteeism in patients from Saudi Arabia. Patients and Methods: This cross-sectional survey incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Some individuals with GI conditions may find their work enjoyable because it provides a focus other than their condition, or perhaps it is linked to opportunities for social support (Huppert & Whittington, 2003;Stansfeld et al, 2013). This is supported by research by Mosli et al (2021) that concluded that a lack of social engagement was predictive of work absence. As employment can still be fulfilling and enjoyable for some despite having a GI condition, further exploration of employment experiences could provide insight into how to better support and encourage employment among those with IBS or IBD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some individuals with GI conditions may find their work enjoyable because it provides a focus other than their condition, or perhaps it is linked to opportunities for social support (Huppert & Whittington, 2003;Stansfeld et al, 2013). This is supported by research by Mosli et al (2021) that concluded that a lack of social engagement was predictive of work absence. As employment can still be fulfilling and enjoyable for some despite having a GI condition, further exploration of employment experiences could provide insight into how to better support and encourage employment among those with IBS or IBD.…”
Section: Discussionmentioning
confidence: 95%
“…'Daily life' was, however, was referred to in six (9%) of the studies included in the final analysis, all of which reported that daily life is affected for those with a GI condition (Buono et al, 2017;Faresjö et al, 2019;García-Sanju an et al, 2018;Kim et al, 2017;Singh et al, 2015;Ung et al, 2013). Employment difficulties were also reported in 25 per cent (N = 17) of the included studies, with absenteeism found to be common among those with IBS or IBD (Ballou et al, 2019;Bernklev et al, 2006;Mosli et al, 2021;Pare et al, 2006;Silk, 2001). To overcome absenteeism, individuals may work from home or reduce their hours and work part time, as was the case for 32 per cent of IBD patients sampled by Ueno et al (2017).…”
Section: Additional Themes or Findingsmentioning
confidence: 99%
“…It was felt that the associated poor quality of life, including lost days of work, social isolation and the mental health burden associated with this condition, is far more important than therapy costs, as they have the potential to significantly improve patient outcomes. In one study, a significant number of participants (43.9%) reported absenteeism as a result of IBD, with persistent abdominal pain, fatigue and difficulty participating in social activities being strong precipitators 21. Additionally, therapies should be offered on an individualised patient basis with the age and comorbidities of patients taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, a significant number of participants (43.9%) reported absenteeism as a result of IBD, with persistent abdominal pain, fatigue and difficulty participating in social activities being strong precipitators. 21 Additionally, therapies should be offered on an individualised patient basis with the age and comorbidities of patients taken into account.…”
Section: Discussionmentioning
confidence: 99%